Long Noncoding RNA LINC00467: Role in Various Human Cancers - Wu, Di; Li, Rongfei; Liu, Jingyu; Zhou, Changcheng; Jia, Ruipeng (Frontiers in Genetics, 2022)
Intricate genetic mutations promote the progression of different cancer types. Long noncoding RNAs (LncRNAs) have been widely demonstrated to participate in the genomic activities of various human cancers. Long intergenic non-coding RNA 467 (LINC00467) is a lncRNA that is upregulated in diverse diseases, especially in several types of cancers. Functional experiments of LINC00467 revealed that LINC00467 overexpression enhanced cell chemoresistance, proliferation, migration and invasion in several types of cancers. Moreover, overexpressed LINC00467 was associated with poor clinical prognosis. The present evidence suggests that LINC00467 may serve as a promising prognostic indicator and become a novel cancer therapeutic target. In this review, we introduce the biologic functions of LncRNAs and describe the molecular mechanism and clinical significance of LINC00467 in detail.